Penggunaan Metode Pembelajaran Drill terhadap Perkembangan Artikulasi Anak Tunarungu - Arifah Nurhadiyati (Journal of Elementary School (JOES), 2019)
This study was used to improve the articulation ability of deaf children of grade 2 elementary school students at SDN Kebonsari 5 Jember through the Drill learning method. The subject of this research supports 6 people, namely 3 male students and 3 female students. Data collection techniques using collection techniques and tests of articulation skills. Analysis of the data used is a comparative technique that compares the results of pre-test and post test. The process of enhancing the ability of articulation is carried out from the pre-test to determine the students' initial abilities. The pre-test shows that the subject has not yet reached the specified KKM, which is 60. Then training is carried out using the Drill method or repetition. After a number of training sessions were carried out. Post test results show students who have increased grades. From the initial number 50 and below, it is now 60 and above. Furthermore, considering the results of Zh (2.05) is greater than the value of Z table 5% (1.96), or Zh (2.05)> Z table (1.96), then Ho is rejected, which means it needs to be added to learning methods dirll towards the development of articulation of deaf children. Conclusion, that is the significance of the significant importance between Bor learning methods on the development of articulation of deaf children. Keywords: Drill, Articulation, Deaf Method